Medikamentózní terapie portální hypertenze - Lata, J (Vnitrni lekarstvi, 2003)
The author presents a list of preparations used to influence portal hypertension resulting from cirrhosis of the liver, in particular in treatment or prevention of haemorrhage from oesophageal varices or gastropathy. The author describes the mechanism of action of drugs administered in acute haemorrhage (vasopressin, terlipressin, somatostatin, octreotide)) and preparations used in primary or secondary prevention of this haemorrhage (beta-blockers, nitrates, newly tested preparations or combinations). In the conclusion are recommendations for practical procedures according to principles of evidence-based medicine.
Keywords: lidé; Hypertension, Portal; portální hypertenze; Humans